Addiction Beyond Substances—What's Up with the DSM?. Issue 1 (3rd April 2017) - Hajela, Raju; Love, Todd
ABSTRACT: This commentary addresses major issues around the diagnosis of addiction with its myriad manifestations, with particular attention to addiction involving Internet use or Internet Addiction (IA). It highlights the inconsistencies and misguided logic used by the American Psychiatric Association (APA) in the DSM-5, particularly in regards to their handling of the phenomenon of addictive behaviors related to Internet use. The APA decision to discard the problem of IA in favor of a fabricated diagnosis based on one of its subtypes, Internet Gaming Disorder (IGD), is adding to the confusion rather than guiding proper assessment and treatment. It is essential that health care providers be more attentive to the needs of patients/clients who have addiction that may involve substances and/or other pathological behaviors, especially related to Internet use.